Body composition and pulmonary function in Cystic Fibrosis - Saba eSheikh; Babette S Zemel; Virginia A Stallings; Ronald C Rubenstein; Andrea eKelly (Frontiers Media S.A., 2014)
Background: Lower body mass index (BMI) is associated with worse pulmonary function in cystic fibrosis (CF). Hypothesis: Lean body mass (LBM) is more strongly associated with pulmonary function than BMI is. Methods: Anthropometrics, body composition by dual x-ray absorptiometry, and pulmonary function were determined in pancreatic insufficient CF (PI-CF) youth. Sex and age-adjusted Z-scores (BMI-Z, LBMI-Z, FMI-Z) were generated for CF and controls. 1) Associations of BMI-Z with LBMI-Z and FMI-Z and 2) age-adjusted associations of BMI-Z, LBMI-Z, and FMI-Z with FEV1%-predicted were tested. Results: 208 PI-CF subjects had lower BMI-Z, LBMI-Z, FMI-Z compared to 390 controls. BMI-Z was associated with lower LBMI-Z (p< 0.0001) in PI-CF. In females, LBMI-Z and BMI-Z were positively associated with FEV1%-predicted; this relationship did not persist for FMI-Z after adjustment for LBMI-Z. In males, only LBMI-Z and BMI-Z were associated with FEV1%-predicted. Conclusions: In PI-CF youth, deficits in LBM were apparent. At lower BMI percentiles, BMI may not accurately depict LBM in PI-CF. In under-nourished PI-CF youth this preservation of FM in preference to LBM is relevant since LBMI-Z, but not FMI-Z, is positively associated with FEV1%-predicted. LBMI is more strongly associated with lung function compared to BMI, especially in the undernourished child and adolescent with PI-CF.